Relative importance of country of service delivery, country of person and country of brand in hybrid service evaluation: a conjoint analysis approach. Issue 7 (21st November 2018) - Aruan, Daniel Tumpal Hamonangan; Crouch, Roberta; Quester, Pascale
Abstract : Purpose: This paper aims to examine the relative importance of country of brand (COB), country of service delivery (COSD) and country of person (COP) in consumer evaluation of hybrid services. Design/methodology/approach: Using data ( N = 1, 071) from Australia, Indonesia and Singapore, a conjoint analysis experimental design explored empirically the importance of country of origin (COO) effects in three service contexts: search, experience and credence. Findings: The analysis reveals that the relative importance of COP was the highest for credence services, while COB was the strongest for experience services. Practical implications: For firms operating offshore, companies must understand that the COO construct is multi-dimensional for services, as it is for tangible products and not limited only to COB as traditionally thought. At least two other distinct dimensions – COSD and COP – can play significant roles as predictors of service quality expectations. Companies must consider the implications of service type, according to the search-experience-credence continuum to inform staffing decisions and managing customer expectations. Originality/value: This research contributes to the literature by extending the understanding of country image effects in the context of hybrid service provisions, particularly in the view of customer expectations of services with multiple country-of-origins. Although there have been several studies examining the effects of COO on services evaluation, no empirical study has examined the effects of multiple COOs simultaneously from the perspective of location where the service is delivered (COSD) and individuals who deliver the service (COP), in addition to the effect of COB origin.